Corporate finance - Helbæk, Morten; Lindset, Snorre; McLellan, Brock (Maidenhead : Open University Press, 2010)
This book covers key topics in the area of corporate finance with a step by step introduction to the most commonly examined principles. Throughout the book, there are tests and practice examples that ensure that you have a clear understanding of the material and are able to put the theory you have learned into practice. The book is split into three main sections: Investments; Risk and Risk Management; Long-Term Financing.
Includes bibliographical references (p. [114]) and index.
nmn 28/05/13
Loans
Keywords: Corporations -- Finance -- Examinations -- Study guides